MENGELOLA PERUBAHAN DI ERA OTONOMI DAERAH SEBAGAI KEBIJAKAN PENYELENGGARAAN PEMERINTAHAN YANG BARU - Arsanti, Tutuk Ari (Fokus Ekonomi, 2006)
This paper is designed to understanding of how and why organizational change and how to mange the change. The trantition from centralization to decentralization is the one of big problem for Indonesia's government to get the change without pain. This paper reviews the emerging literatur, seeking to get understanding of process influencing change suistainability. According to this paper can guide the government in successfully managing organization structure change from centralization to decentralization.Keywords: Centralization, Decentralization, Change Management.